2016
DOI: 10.1016/j.cmi.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Australian newborn calf carcasses at slaughter with Clostridium difficile

Abstract: In North America and Europe, reports of a genetic overlap between toxigenic strains of Clostridium difficile isolated from humans, livestock and retail meat suggest that food-borne transmission may be occurring. We investigated the prevalence, concentration and genetic diversity of C. difficile on the carcasses (n = 300) and in the faeces (n = 30) of neonatal veal calves at three abattoirs in Australia in 2013. Selective culture (both direct and enrichment) was performed, and all isolates were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 29 publications
1
43
1
Order By: Relevance
“…In observations from the USA and Canada, RT078 was also reported from calf samples [7,31]. In addition, 4 RTs (127, 288, 033, and 126) with binary toxin-positive accounts for 70.3% (71/101) of isolates from a calf farm in Australia [32]. In this study, three STs (ST11, 3, and 468) and 6 RTs (RT126, ICDC050, ICDC052, ICDC094, RT078, and RT220) were identified.…”
Section: Discussionmentioning
confidence: 95%
“…In observations from the USA and Canada, RT078 was also reported from calf samples [7,31]. In addition, 4 RTs (127, 288, 033, and 126) with binary toxin-positive accounts for 70.3% (71/101) of isolates from a calf farm in Australia [32]. In this study, three STs (ST11, 3, and 468) and 6 RTs (RT126, ICDC050, ICDC052, ICDC094, RT078, and RT220) were identified.…”
Section: Discussionmentioning
confidence: 95%
“…However, unlike the Australian dairy industry where there remains a consumer demand for neonatal veal products (Knight et al, 2013, 2016), suckling age piglets are not slaughtered for meat on a large scale and are unlikely to contribute to a persistent or substantial community reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…C. difficile is particularly prevalent in production animals such as piglets and calves both in Australia (Knight et al, 2014, 2016) and other countries (Hensgens et al, 2012; Rodriguez et al, 2016). Furthermore, genetically similar strains of C. difficile (characterized by RT, MLST, MLVA, and WGS), particularly toxinotype V (RT078), have been recovered from humans, production animals and retail meat, fuelling speculation that CDI may have a foodborne or zoonotic etiology (Rupnik and Songer, 2010; Knetsch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, C. difficile was not detected in any of the 20 feline raw foods purchased in France (Bouttier et al, 2010). The isolation of C. difficile from raw meat for human consumption has been well documented (Bouttier et al, 2010;De Boer et al, 2011;Jöbstl et al, 2010), and recent studies showed that the contamination of carcass and offal surfaces can already occur during from the slaughter of livestock and poultry (Bakri, 2018;Guran & Ilhak, 2015;Knight, Putsathit, Elliott, & Riley, 2016). Therefore, the consumption by pets of raw meat, raw offal and other animal by-products may be a possible source of C. difficile intestinal colonization.…”
Section: Discussionmentioning
confidence: 99%